HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN POLA MAKAN KLIEN DENGAN PENYAKIT DIABETES MELLITUS - Tigor Abdurrahman Thomy; Mutmainah Handayani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Diabetes mellitus is a disease characterized by high levels of sugar (glucose) in the blood, because the body is unable to release or use insulin adequately. There are several risk factors for diabetes, namely: diet, knowledge, offspring, obesity, infection, age, other diseases, drug consumption, and genetic syndromes. (Sutedjo, 2010). From the Medical Record of Pusri Hospital in Palembang City, the case of Diabetes Mellitus in 2013 was 728 cases. In 2014 the number of patients was 742 cases, in 2015 there were 774 cases. (Pusri Hospital Medical Record). The purpose of this study is to know the relationship between knowledge and dietary patterns of clients simultaneously with Diabetes Mellitus in the Outpatient Installation of Pusri Palembang Hospital in 2017. This type of research uses a cross sectional approach. Test the statistics used using the Chi-Square test. And the sample in this study was taken with a total population technique of 30 people. Bivariate analysis states that there is a significant relationship between diet and diabetes mellitus where p value =0.002 is smaller than ? = 0.05 and there is no significant relationship between knowledgesimultaneously with the incidence of diabetes mellitus. Where p. value = 0.069 is greater with ? = 0.05. Conclusions from this study that there is a significant relationship between diet and the incidence of diabetes mellitus and there is no significant relationship between knowledge with the incidence of diabetes mellitus. Suggestions from this study to the hospital. Pusri Palembang is in providing quality health services that should be improved in providing information and is expected to improve access to health services, especially regarding diabetes mellitus